Pengaruh Media Pendingin PKO Terhadap Kekuatan Tarik Hasil Pengelasan SMAW Pada Baja S45C - Indah Purnama Putri; Adi Febrianton (Politeknik Kampar, 2023)
The use and utilization of steel in the industrial world is very extensive because steel has unique properties, especially its strength. All tooling equipment cannot be separated from the engineering process and repair in the event of damage, namely by welding. One of the things that must be considered in welding is the cooling process. The purpose of the research was conducted to determine the effect of the cooling process on welding on the tensile strength of medium carbon steel using palm waste as a cooling medium. Tensile test samples were made with 3 variations of cooling media (PKO 100%, PKO75%, PKO 50%) using a HUNG TA HT-8503 machine. The highest tensile strength value was obtained from the 75% PKO variation with a tensile strength value of 345.58 Mpa. While the lowest tensile strength value is obtained from the 50% PKO variation with a tensile strength value of 232.28 Mpa.